2021
DOI: 10.21744/lingcure.v5ns1.1347
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the role of digitalization to business model and innovation: economics and business review studies

Abstract: This paper analyzed the role of the digitalization approach in innovating business operating models in Indonesia. We chose a review research approach on the findings of economic and business journals that we searched electronically based on Google application data. We focus on findings from international journals that discuss how digitalization plays a role in innovation models of profitable and sustainable business operations. We reviewed papers published in the last ten years (2010 to 2020) using data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 66 publications
0
6
0
2
Order By: Relevance
“…Most researchers and policymakers defined it based on total investment, annual sales and number of employees. Generally, the definition is based on either a single criterion or multiple criteria (Hendriarto, 2021;Shcherbyna et al, 2021).…”
Section: Small and Medium Enterprises (Smes)mentioning
confidence: 99%
“…Most researchers and policymakers defined it based on total investment, annual sales and number of employees. Generally, the definition is based on either a single criterion or multiple criteria (Hendriarto, 2021;Shcherbyna et al, 2021).…”
Section: Small and Medium Enterprises (Smes)mentioning
confidence: 99%
“…e overall index system constructed includes five aspects: transportation capacity, storage capacity, service capacity, distribution capacity, and informatization level. AHP is used to determine the weight [18]. Molina et al constructed the system dynamics model of the three-level agricultural product supply chain under the regular procurement mode, studied the bullwhip effect of the supply chain and the relationship between the cost and the inventory adjustment coefficient, and found that retailers and wholesalers are more sensitive to the change of the inventory adjustment coefficient, and reasonable inventory objectives and inventory adjustment strategies can effectively reduce the bullwhip effect of the supply chain [19].…”
Section: Related Workmentioning
confidence: 99%
“…Banyak perusahaan telah merancang sistem pengembangan SDM berbasis teknologi digital (Hendriarto, 2021) sebagai model bisnis mutakhir untuk berinovasi. Namun sayangnya, karena berbagai sebab (Bjerke-Busch & Aspelund, 2021) lembaga pemerintah belum sepenuhnya mengadopsi penggunaan teknologi digital untuk tujuan efisiensi dan efektivitas pengembangan SDM.…”
Section: Pendahuluanunclassified